Facilitation and competition interact with seed dormancy to affect population dynamics in annual plants. Issue 4 (9th September 2019) - Leverett, Lindsay D.; Shaw, Allison K.
Abstract: Seed dormancy increases population size via bet‐hedging and by limiting negative interactions (e.g., competition) among individuals. On the other hand, individuals also interact positively (e.g., facilitation), and in some systems, facilitation among juveniles precedes competition among adults in the same generation. Nevertheless, studies of the benefits of seed dormancy typically ignore facilitation. Using a population growth model, we ask how the facilitation–competition balance interacts with seed dormancy rate to affect population dynamics in constant and variable environments. Facilitation increases the growth rate and equilibrium size (in both constant and variable environments) and reduces the extinction rate of populations (in a variable environment), and a higher rate of seed dormancy allows populations with facilitation to reach larger sizes. However, the combined benefits of facilitation and a high dormancy rate only occur in large populations. In small populations, weak facilitation does not affect the growth rate, but does induce a weak demographic Allee effect (where population growth decreases with decreasing population size). Our results suggest that facilitation within populations can interact with bet‐hedging traits (such as dormancy) or other traits that mediate density to affect population dynamics. Further, by ensuring survival but limiting reproduction, ontogenetic switches from facilitation to competition may enable populations to persist but limit their maximum size in variable environments. Such intrinsic regulation of populations could then contribute to the maintenance of similar species within communities. Abstract : Here we model seed dormancy in an annual plant, examining the effect of facilitation among seedlings and competition among adults. We find that populations experiencing facilitation among juveniles followed by competition among adults perform better if they have a high rate of seed dormancy, regardless of variation in the environment. However, a high rate of seed dormancy in populations experiencing a small degree of facilitation can be detrimental by inducing a weak demographic Allee effect that increases extinction risk.